2009
DOI: 10.2528/pierm09031804
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Determining the Scattering of Linear Polarized Element Arrays

Abstract: Abstract-A new method for analyzing the RCS of array antennas is presented in this paper. In the proposed method, the total RCS of the array can be simply decomposed to array RCS factor and element RCS factor. By this decomposition, the effects of the array distribution and antenna elements on scattering can be clearly exhibited. Thus, the analyzing of scattering characteristic of array antennas becomes easier. Moreover, proposed method has good compatibility for calculating the RCS of the array antennas with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…According to the RCS definition [2], the antenna RCS is the product of σnormale and σnormala that denote the scattering element factor and scattering array factor, respectively. The path length between radar signal and element m is rm away.…”
Section: Structure and Scattering Array Factor Coupling Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the RCS definition [2], the antenna RCS is the product of σnormale and σnormala that denote the scattering element factor and scattering array factor, respectively. The path length between radar signal and element m is rm away.…”
Section: Structure and Scattering Array Factor Coupling Modelmentioning
confidence: 99%
“…Assume that the position errors in the x , y , and z directions satisfy the normal distribution with mean of 0 and standard derivation of λ/10. Considering the scattering element factor σnormale of half‐wavelength dipole [2], the scattering pattern function can be obtained.…”
Section: Verification Of Coupling Modelmentioning
confidence: 99%
“…The polarization state of a beam of light is traditionally described by a vector I = (I, Q, U, V ) T composed of four Stokes parameters (T means transpose) [14][15][16][17][18][19][20][21][22][23]. The first Stokes parameter, I, is the intensity, while the other three parameters describe the polarization state of the beam.…”
Section: Theory and Definitionsmentioning
confidence: 99%
“…Then, based on the expression in Ref. 3, a method was presented in Ref. 4 for synthesizing desired scattering pattern by adjusting the dipole positions.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method might not be used to automatically control the radar cross section (RCS) levels of the main lobe and the sidelobes. To overcome this problem, in a way the similar to the radiation pattern multiplication method [2], Lu et al [3] indicated that the RCS of an array can also be expressed as the product of an array factor and an element factor. Then, based on the expression in Ref.…”
Section: Introductionmentioning
confidence: 99%